Facile synthesis of N-substituted maleimides - Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Chaudhary, Preeti M. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
A simple and efficient method for the synthesis of N-substituted malemides from the corresponding maleamie acids under the phase transfer catalysis has been described
Keywords: Maleamic acids; maleimides; phase transfer catalysis; synthesis

First regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles - Rode, Navnath D.; Sonawane, Amol D.; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P. (Tetrahedron Letters, 2015)
The regioselective iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles is described for the first time. The iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles using molecular iodine afforded diiodo-compound which on Cul-catalyzed intramolecular C-N coupling reaction gave six-membered 2-aryl-51141,2,4]triazolo[5,1-b][1,3]thiazines, whereas, the five membered 3-aryl-5,6-dihydrothiazolo[2,3-c][1,2,4]triazoles were obtained exclusively when the iodocyclization reaction of 3-aryl-5-(prop-2-ynylthio)-1H-1,2,4-triazoles was carried out using NIS. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Iodocyclization; Regloselective; Thiazine; Triazole